THE RELATIONSHIP BETWEEN LEARNER AUTONOMY AND ACADEMIC SELF-EFFICACY AMONG ENGLISH MAJOR STUDENTS IN HUBEI PROVINCE - Dong, Zhihao; Mustapha, Siti Maziha (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this paper is to explore the current level of learner autonomy and academic self-efficacy and relationship between learner autonomy and academic self-efficacy amongst English major students. A total number of 443 English majors students from eight universities in Hubei Province were chosen as respondents through two steps, stratified sampling and simple random sampling. In this study, two questionnaires were adopted to gather data from the 443 chosen respondents. After the data collection, SPSS 24.0 was used to process the data set to generate descriptive statistics and then Pearson product moment correlation analysis was utilized to find out the correlation between earner autonomy and academic self-efficacy. The outcomes of this research show that: firstly, the overall levels of English major students’ learner autonomy and academic self-efficacy are both moderate; secondly, there is a significant and positive correlation between English major students’ learner autonomy and academic self-efficacy, with the correlation coefficient value being 0.462; thirdly, there is a significant and positive correlation between the five dimensions of English major students’ learner autonomy and academic self-efficacy, with the correlation coefficient value being 0.421, 0.450, 0.279, 0.334 and 0.477 respectively; fourthly, there is a significant and positive correlation between the dimensions of English major students’ academic self-efficacy and learner autonomy with the correlation coefficient value being 0.423, 0.342 respectively. On the basis of the results of the investigation, this study further puts forward some strategies concerning the improving of English major students’ academic self-efficacy and learner autonomy. In addition, some recommendations for future research are also put forward.